Universal nature of rapid evolution of conservative gravity and turbidity currents perturbed from their self-similar state - Zúñiga, Santiago Luciano (2022)
The results of six highly resolved direct and large eddy simulations of gravity and conservative turbidity currents are presented to illustrate the point that the rapidly varying evolution of these currents follow a universal cyclic sequence of four states. The demarcation between these four states is determined by the bulk Richardson number and the acceleration/deceleration of the flow. We describe in detail the identification process of these states, together with the associated three-dimensional structure of the current. The exact depth-averaged momentum balance is computed and used to explain the intricate details of the nonmonotonic rapid evolution of the current between the different states. Finally, the balance of turbulent kinetic energy and concentration flux are computed to explain how and why the current evolves through the cyclic sequence of states. We also explore the mechanism by which the current can exit the cyclic sequence and slowly evolve towards self-similar supercritical or subcritical states.